UJIDAYA HASIL PENDAHULUAN KLON-KLON UBIJALAR (Ipomoea Batatas L.) BERDAGING UNGU - Hidayat, Fariz Nur; Lestari, Sri Umi; Indawan, Edyson (Universitas Tribhuwana Tunggadewi, 2017)
Selection to be implemented on the ground tuber yield entrisol Wringinsongo Village Tumpang subdistrict Malang. Randomized block design MK II, 2014. Materials studied as much as 40 purple sweet potato clones, divided into three blocks, and each block planted three varieties (check). Each clone planted 20 plants by bunds. Phonska fertilized gived with a dose of 300 kg / ha. Characters are observed are the number and weight of tuber by mound, tuber dry matter content, color of skin, flesh, the uniformity of the shape and size of the tuber. Selection purposes is to obtain clones of sweet potato varieties with the above results Antin 3 and have high anthocyanin score >5. Chosen 12 clones with the tuber yield 24.38 to 33.75 kg / ridges (from 19.50 to 27.00 t / ha), namely RIS 10053-01, 10233-01 RIS, MSU 10001-08, 10003-54 MSU, MSU 10010-50, 10010-80 MSU, MSU 10017-02, 10018-39 MSU, MSU 10021-26, MSU 10025-29, 10031-12 MSU and MSU 10031-16. Retrieved 4 clones were selected with high anthocyanin levels are RIS 10233-01 (U6 dark), MSU 10001-08 (U7 very dark), MSU 10010-50 (U6 dark), and MSU 10018-39 (U6 dark). Seleksi untuk hasil umbi dilaksanakan pada tanah entrisol Desa Wringinsongo Kecamatan Tumpang, Kabupaten Malang menggunakan rancangan acak kelompok MK II 2014. Bahan yang diteliti sebanyak 40 klon ubijalar ungu, dibagi menjadi tiga blok dan masing-masing blok ditanam tiga varietas pembanding (cek). Setiap klon ditanam 20 tanaman per guludan.Pertanaman dipupuk Phonska dengan dosis 300 kg/ha. Karakter yang diamati adalah jumlah dan bobot umbi per guludan,kadar bahan kering umbi, warna kulit, daging, serta keseragaman bentuk dan ukuran umbi. Tujuan seleksi adalah untuk mendapatkan klon-klon ubijalar dengan hasil di atas varietas Antin 3 dan memiliki skor antosianin tinggi >5.Terpilih 12 klon dengan hasil umbi 24,38?33,75 kg/guludan (19,50?27,00 t/ha) yaitu RIS 10053-01, RIS 10233-01, MSU 10001-08, MSU 10003-54, MSU 10010-50, MSU 10010-80, MSU 10017-02, MSU 10018-39, MSU 10021-26, MSU 10025-29, MSU 10031-12, dan MSU 10031-16. Diperoleh 4 klon yang terpilih dengan level antosianin tinggi adalah RIS 10233-01 (U6 gelap), MSU 10001-08 (U7 sangat gelap) ,MSU 10010-50 (U6 gelap), dan MSU 10018-39 (U6 gelap).